2-methyl-6,6-bis(trlfluoromethyl)cyclohex-3-ene-1-carbaldehyde: reactivity and application as a model for the preparation of 16,16,16,17,17,17-hexafluororetinal analogs - Boichut, S.; Boyer, C.; Burger, K.; Haas, A.; Merz, K.; Pages, T.; Wallmichrath, T. (Журнал органічної та фармацевтичної хімії, 2008)
New approaches to 16,16,16,17,17,17-hexafluororetinal and analogs, via 2-methyl-6,6-bis(trifluoromethyl)cyclohexanone and 2-methyl-6,6-bis(trifluoromethyl)cyclohex-1-ene-1 -carbaldehyde (7,7,7,8,8,8-hexafluoro-β-cyclocitral) are presented. An efficient synthesis for 2-methyl-6,6-bis(trifluoromethyl)-cyclohex-3-ene-1-carbaldehyde starting from hexafluoroacetone has been described and used for preparing reactive building blocks. The crystal structures of 6, 15 and 23 have been provided and the influence of the bis(trifluoromethyl)-group on bond lengths and angles have been discussed.